Portrayals of disability in traditional Sanni Yakuma rituals of Sri Lanka: A cultural analysis - Madushanka, M.A.D. (University of Colombo, 2025)
The Sanni Yakuma, a ritual healing performance in Sri Lanka’s traditional yakadura (exorcism) practice, features a series of masks and characters, each representing a particular illness or affliction. Among these, several Sanni embody physical, sensory, and cognitive disabilities. This study examines how such disabilities are portrayed within the Sanni tradition and the cultural meanings attached to these depictions, situating them within the broader context of Sri Lankan beliefs about illness, misfortune, and the supernatural. This research is based on secondary data collected from existing ethnographic studies and scholarly analyses of the Sanni Yakuma. Thematic content analysis was conducted focusing on mask design, symbolic gestures, and narrative roles. Prominent disability-related sanni include: Andha Sanniya (blindness, depicted with closed or hollow eyes), Kana Sanniya (partial blindness, with one eye exaggerated), Golu Sanniya (mute or speech-impaired, shown with sealed lips or exaggerated mouth), Butha Sanniya (mental illness or disorientation, with asymmetrical facial features), and Pissu Sanniya (madness, represented through erratic gestures). These portrayals use visual exaggeration, posture, and movement to signify impairments, raising questions about whether they reinforce stigmatizing views or act as symbolic elements in a healing ritual. Humour, fear, and empathy often intersect in shaping audience responses. The findings suggest that while the Sanni Yakuma traditionally conceptualised disability as a manifestation of demonic influence requiring ritual intervention, it also served as a communal space for engaging with difference and misfortune. These portrayals simultaneously preserve a form of intangible heritage and risk perpetuating stereotypes about disability. Understanding these dual roles is essential for appreciating the cultural complexity of the Sanni Yakuma and for considering its place within contemporary conversations on disability and heritage preservation in Sri Lanka.
Keywords: Disability; Mask art; Sanni Yakuma; Stereotypes